Ph. Corrigan, D. Sayer, The Great Arch. English State Formation as Cultural Revolution, 1985 - Adam Czarnota (Czasopismo Prawno-Historyczne)
Recenzja: Philip Corrigan, Derek Sayer, The Great Arch. English State Formation as Cultural Revolution, Basil Blackwell, Oxford 1985